HUBUNGAN MOTIVASI BELAJAR DAN INTENSITAS BIMBINGAN BELAJAR ORANG TUA DENGAN PRESTASI BELAJAR PKN SISWA KELAS V SD SEGUGUS II KALASAN SLEMAN - Ririh Rahayu Retnoningsih; Al. Sugijanto (Universitas Sarjanawiyata Tamansiswa, 2018)
This research aimed to measure correlation between (1) learning motivation on civic education’s learning achievement , (2)parental guidance’s intensityof education oncivic education’s learning achievement, (3) learning motivation and parental guidance’s intensityof education oncivic education’s learning achievement. This research was a correlational study type of research. Data were collected using questionnaire instrument and documentation. Data in this study were analyzed using descriptive analysis and then hypothesis tested using Product Moment correlation followed by two predictor’s multiple regretion which were preceded with normality, independence, and linearity tested. The Result of this research indicated (1) There was positive and significant relationship between learning motivation with civic education’s learning achievement and the correlation coefficient value was = 0,213 >0,195, (2) There was positive and significant relationship between parental guidance’s intensityof education oncivic education’s learning achievement and the correlation coefficient value was= 0,202 >0,195, (3) There was significant relationship between learning motivation and parental guidance’s intensityof education oncivic education’s learning achievement, and then the F value was Fregresi = 4,204 > Ftabel 3,09. This was mean that the result of this research can be applied for five grade’s elementary school students in Gugus II Kalasan, Sleman. Determination coefficient value was 0,273, this mean that civic education’s learning achievement can be explained by learning motivation and parental guidance’s intensityof education by 7,48%, while the rest of 92,52% was explained by the other factors that excluded to regretion model.